2000
DOI: 10.1302/0301-620x.82b7.0821065
|View full text |Cite
|
Sign up to set email alerts
|

Precision of the measurements of periprosthetic bone mineral density in hips with a custom-made femoral stem

Abstract: Our aim was to determine the precision of the measurements of bone mineral density (BMD) by dual-energy x-ray absorptiometry in the proximal femur before and after implantation of an uncemented implant, with particular regard to the significance of retro-and prospective studies.We examined 60 patients to determine the difference in preoperative BMD between osteoarthritic and healthy hips. The results showed a preoperative BMD of the affected hip which was lower by a mean of 4% and by a maximum of 9% compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…It is accepted that most of the remodelling is established at the end of the first postoperative year, reaching a balance in BMD from this moment onwards (Sychter and Engh, 1996;Martini et al, 2000;Gibbons et al, 2001). The obtained results suggest that this stability appears between the 6th and 12th month, when the changes in BMD reflect the biochemical response of the bone, in accordance to Wolff's law.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…It is accepted that most of the remodelling is established at the end of the first postoperative year, reaching a balance in BMD from this moment onwards (Sychter and Engh, 1996;Martini et al, 2000;Gibbons et al, 2001). The obtained results suggest that this stability appears between the 6th and 12th month, when the changes in BMD reflect the biochemical response of the bone, in accordance to Wolff's law.…”
Section: Discussionsupporting
confidence: 59%
“…These changes explain that with first generation cemented stems the losses in density reached up to 45% (Sychter and Engh, 1996;McAuley et al, 2000;Sychter et al, 2002), with second generation stems still reaching between 20% and 25% at the end of the first or second year (Ka¨rrholm et al, 2002) and with tapered stems decreases between 10% and 30% were found with proximal predominance (Gibbons et al, 2001;Schmidt et al, 2004). Custom made implants had decreases in proximal areas of 10-15% at the end of the first year (Zerahn et al, 1998;Martini et al, 2000); femoral stems with reduced stiffness showed 15% reduction in the calcar at the end of the second year (Ka¨rrholm et al, 2002;Nagi et al, 2006).…”
Section: Discussionmentioning
confidence: 92%
“…1,2,4,5,6,20 Other studies have reported a BMD loss of greater than 50% in the calcar region. 5 Studies on cementless stems have shown a recovery of bone density after an initial postoperative bone loss.…”
Section: Discussionmentioning
confidence: 98%
“…11 HA-coated implants have a good clinical and radiological outcome with more favourable bone remodelling and implant fixation when compared with porous-coated implants. 4,5,12,13,14 Histological analyses in cadaveric specimens have shown sound proximal and distal HA stem-bone osteointegrations in a relatively short period. 15,16 Such findings could reduce proximal stress shielding and provide a circumferential barrier to wear debris that induces osteolysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation